Valuing water: an approach to the hydrosocial territories in Mexico - Acosta, Eliana (2026)
Based on anthropological knowledge and political ecology, the article aims to examine the plurality of hydrosocial territories in Mexico and to account for the conception, use, and management of water in contexts of dispute over this vital liquid and territory. Specifically, it delves into the valuation of water in two regions of the state of Puebla: The Northwestern Sierra and the Cholultecas and Volcanoes region. Through ethnographic work and a comparative approach, it is shown that among Indigenous and native peoples, water can be identified as a use-value that differs from a commodified or market-based valuation. Drawing on springs and norias (traditional wells), the article highlights that water and territory not only constitute an essential foundation for the reproduction of existence, but also generate a complex web of creative actions, social interrelations, and cosmopolitical connections beyond the human realm. In the context of the historical continuity of accumulation by dispossession, land and water enter a contested arena that activates a process of valuing one’s own and asserting collective rights.